LEGAL RIGHTS OF HOMELESS CHILDREN AND SINGLE MOTHERS - GENERAL OVERVIEW - Lia Chiglashvili (European Scientific Journal, ESJ, 2015)
The article includes a review-analysis of the issues of the legal status of children and single mothers. In particular, this concerns legal rights of underprivileged children and single mothers who regularly require the support and contribution of the state. Although international law made an impact on the creation of Georgian legislative defense mechanisms of the children's and women's' rights, some norms are only partly fulfilled. This is the main purpose of the article, based on European legislation, to quickly and effectively implement those rights in Georgia and legally regulate social and moral issues of homeless children and single mothers.